Artificial Intelligence Empowers the Integrated Development of Legal Education: Challenges and Responses - Bo Ma; Yuhuan Hou (International Society of Philosophy and Cosmology, 2021)
Artificial intelligence is profoundly changing human social life, and the integration between artificial intelligence and law continues to deepen. Artificial intelligence has brought new impetus for legal education from three dimensions: providing new technologies, establishing new models, and shaping new paradigms. At present, it is still at the exploratory stage on how to position the goal of cultivating versatile professionals of "artificial intelligence + law," how to improve the competence of teachers, and how to integrate the curriculum system. As one of the important contents of the paradigm transformation of "New Liberal Arts" education, legal education must also upgrade the concept of cultivating professionals, make full use of the support of big data, artificial intelligence, and other new technologies, clarify the goal of cultivating versatile professionals who "have the ability of legal thinking can use artificial intelligence technology," bolster the ranks of teachers who not only "understand the technology" but also can "foster a new generation of people with sound values and ethics," and construct the interdisciplinary, integrated AILE theoretical and practical curriculum systems, for the purpose of responding to the development trend of the transformation of liberal arts education in the new era, and providing intellectual support for cultivating professionals to meet the development needs of the country in the new era.